Characterization of PGRP-S1 from the oriental armyworm, Mythimna separata. (January 2019) - Yang, Pei-Jin; Zhan, Ming-Yue; Yang, Li-Ling; Liu, Qiong-Qiong; Xu, Yang; Pan, Yue-Min; Rao, Xiang-Jun
Abstract: Peptidoglycan is the key component forming the backbone of bacterial cell wall. It can be recognized by a group of pattern recognition receptors, known as peptidoglycan recognition proteins (PGRPs) in insects and higher animals. PGRPs may serve as immune receptors or N-acetylmuramoyl-L-alanine amidases (EC 3.5.1.28). Here, we report the characterization of a short PGRP, PGRP-S1, from the oriental armyworm, Mythimna separata . MsePGRP-S1 cDNA encodes a protein of 197 amino acids (aa) with a PGRP domain of about 150 aa. MsePGRP-S1 was expressed in several tissues of naïve larvae, including hemocytes, midgut, fat body and epidermis. Bacterial challenges caused variable changes in different tissues at the mRNA level. The recombinant protein bound strongly to Staphylococcus aureus and purified peptidoglycans from Staphylococcus aureus and Bacillus subtilis . It can inhibit the growth of gram-negative and gram-positive bacteria by disrupting bacterial surface. It can degrade peptidoglycans from Escherichia coli and Staphylococcus aureus . Taken together, these data demonstrate that M. separata PGRP-S1 is involved in defending against bacteria. Highlights: The cDNA of Mythimna separata PGRP-S1 was cloned. The expression profile, phylogenetic relationship and structure were analyzed. PGRP-S1 can bind to Dap-type and Lys-type peptidoglycans. PGRP-S1 has amidase activity. PGRP-S1 has bacteriolytic activity.